'The people's choice': popular (il)legitimacy in autocratic Cameroon*. Issue 4 (23rd November 2017) - Letsa, Natalie Wenzell
Abstract: While many analysts assume that the autocratic regime of Paul Biya is deeply unpopular amongst ordinary Cameroonians, there is almost no existing analysis of public opinion in Cameroon. In fact, Cameroonians are deeply divided in their beliefs about politics; while many view the government as democratic and legitimate, others see the regime as entirely autocratic. What explains these fundamental divides in beliefs? While existing theories point to demographic factors as the most important predictors of political opinions, this article argues that in autocratic regimes, political geography is even more important to understanding these divides. Political parties in autocratic regimes develop opposite narratives about the legitimacy of the state, and regardless of education, partisanship, age, or ethnicity, citizens living in party strongholds are far more likely to adopt these narratives than citizens outside of strongholds. Understanding these divides is critical to explaining regime legitimisation in Cameroon, and African autocracies more broadly.